Volunteering: A Study of Psychological Attribute Related to Indonesian Emerging Adult Volunteer Motivation - Sugiarti Agus Musabiq; Adisya Adisya; Adrianisa Kamila Shabrina; Aviva Lutfiana; Bianda Retno Widyani; Daeng Azizah Rahmatia; Mugi Silih Mulyadi; Rayhanni Rahman; Mutiara Sintesana Prasetyo (Journal of Educational, Health and Community Psychology, 2020)
Numerous problems in Indonesia, ranging from poverty to natural disasters, require that all parties participate in solving the problems. For this reason, volunteering can be the human resource that helps to solve these problems. This idea is also supported by data showing that younger Indonesians also like to volunteer. This study aimed to determine the relationship between volunteer motivation dimensions with psychological attributes, such as personality traits, happiness, interpersonal trust, narcissistic personality, self-efficacy, purpose in life, and psychological distress on volunteers aged 18–29 years old (emerging adults). The motivation to volunteer was the main variable and had six dimensions, namely values, social, career, knowledge, understanding, and enhancement motives. This correlational study had 1712 respondents. All the measuring instruments were already adapted to Bahasa Indonesia. The results showed all the variables of psychological attributes have a significant relationship with one or more motivations to volunteer.Keywords Volunteering motivation, Happiness, Purpose of life, Personality, Emerging adults